Customer Satisfaction in Services Sector: The Strategic Interaction Between Service Quality, Price Perception and Perceived Value in Makeup Rahmah - Rahmah Nuryani; Hari Muharam; Sufrin Hannan (Asosiasi Ahli Administrasi Indonesia, 2026)
This study was conducted to examine the role of perceived value in mediating the influence of service quality and price perception on customer satisfaction at Makeup Rahmah. The research employed a quantitative method with a survey approach, where data were collected through questionnaires distributed to 188 customers selected using a simple random sampling technique. The data were analyzed using SPSS version 25 and LISREL 8.80 with Structural Equation Modeling (SEM) to test both direct and indirect effects among variables. The results show that service quality has a significant effect on customer satisfaction, price perception has a significant effect on customer satisfaction, perceived value does not have a direct effect on customer satisfaction, and perceived value is not able to mediate the influence of service quality and price perception on customer satisfaction. The practical implications of this research suggest that makeup service providers, particularly Makeup Rahmah, should prioritize improving service quality, setting transparent and competitive prices, and enhancing perceived value creation to maintain customer loyalty and long-term satisfaction. The novelty of this study lies in its specific focus on the makeup service sector in the local Indonesian context (Ciampea, Bogor), which has rarely been examined using SEM with perceived value as a mediating variable. This research provides empirical evidence that distinguishes it from previous studies on service quality and price perception, offering new insights into consumer behavior in the beauty service industry.